Converting hip and knee arthroplasty cases to same-day surgery due to COVID-19. (21st July 2021) - Cherry, Ahmed; Montgomery, Spencer; Brillantes, Jacqueline; Osborne, Tasha; Khoshbin, Amir; Daniels, Timothy; Ward, Sarah E.; Atrey, Amit
Abstract : Aims: In 2020, the COVID-19 pandemic meant that proceeding with elective surgery was restricted to minimize exposure on wards. In order to maintain throughput of elective cases, our hospital (St Michaels Hospital, Toronto, Canada) was forced to convert as many cases as possible to same-day procedures rather than overnight admission. In this retrospective analysis, we review the cases performed as same-day arthroplasty surgeries compared to the same period in the previous 12 months. Methods: We conducted a retrospective analysis of patients undergoing total hip and knee arthroplasties over a three-month period between October and December in 2019, and again in 2020, in the middle of the COVID-19 pandemic. Patient demographics, number of outpatient primary arthroplasty cases, length of stay for admissions, 30-day readmission, and complications were collated. Results: In total, 428 patient charts were reviewed for October to December of 2019 (n = 195) and 2020 (n = 233). Of those, total hip arthroplasties (THAs) comprised 60% and 58.8% for 2019 and 2020, respectively. Demographic data was comparable with no statistical difference for age, sex, contralateral joint arthroplasty, or BMI. American Society of Anesthesiologists grade I was more highly prevalent in the 2020 cohort (5.1-times increase; n = 13 vs n = 1). Degenerative disc disease and fibromyalgia were less significantly prevalent in the 2020 cohort. There was a significant increase in same day discharges for non-direct anterior approach THAs (two-times increase) and total knee arthroplasty (ten-times increase), with a reciprocal decrease in next day discharges. There were significantly fewer reported superficial wound infections in 2020 (5.6% vs 1.7%) and no significant differences in readmissions or emergency department visits (3.1% vs 3.0%). Conclusion: The COVID-19 pandemic meant that hospitals and patients were hopeful to minimize the exposure to the wards, and minimize strain on the already taxed inpatient beds. With few positives during the COVID-19 crisis, the pandemic was the catalyst to speed up the outpatient arthroplasty programme that has resulted in our institution being more efficient, and with no increase in readmissions or early complications. Cite this article: Bone Jt Open 2021;2(7):545–551.